Investigating value-laden leadership styles among family business owners - E. Venter; S. M. Farrington (South African Journal of Business Management, 2016)
Given the need for a different approach to leadership, as well as the need for further investigation on leadership among family businesses, this study investigates several value-laden leadership styles among family businesses. More specifically the primary objective is to establish the levels of Servant, Ethical, Authentic, and Participative leadership displayed by family business owners and the influence thereof on the Perceived business performance of the family business. A survey was undertaken and 266 usable questionnaires were returned from 133 family business owners and 133 from family business employees. The data analysis involved calculating descriptive statistics and undertaking t-tests. Multiple regression analysis (MRA) was done to test the hypothesised relationships. Although the MRA analysis revealed no statistically significant relationships between the leadership styles investigated and Perceived business performance, the vast majority of respondents agreed that the styles investigated were displayed by the family business owners. For both sample groups Ethical leadership returned the highest mean score, followed by Servant and Participative leadership. The importance of these value-laden leadership styles to family businesses is thus highlighted, contradicting the literature that family businesses owners are often autocratic in their leadership style. In addition, increased clarity on the effectiveness of these value-laden leadership styles within the context of family business is provided.
Keywords: 650